The transcriptional program during germinal center reaction - a close view at GC B cells, Tfh cells and Tfr cells - Betzler, Annika C.; Ushmorov, Alexey; Brunner, Cornelia (Frontiers in Immunology, 2023)
The germinal center (GC) reaction is a key process during an adaptive immune response to T cell specific antigens. GCs are specialized structures within secondary lymphoid organs, in which B cell proliferation, somatic hypermutation and antibody affinity maturation occur. As a result, high affinity antibody secreting plasma cells and memory B cells are generated. An effective GC response needs interaction between multiple cell types. Besides reticular cells and follicular dendritic cells, particularly B cells, T follicular helper (Tfh) cells as well as T follicular regulatory (Tfr) cells are a key player during the GC reaction. Whereas Tfh cells provide help to GC B cells in selection processes, Tfr cells, a specialized subset of regulatory T cells (Tregs), are able to suppress the GC reaction maintaining the balance between immune activation and tolerance. The formation and function of GCs is regulated by a complex network of signals and molecules at multiple levels. In this review, we highlight recent developments in GC biology by focusing on the transcriptional program regulating the GC reaction. This review focuses on the transcriptional co-activator BOB.1/OBF.1, whose important role for GC B, Tfh and Tfr cell differentiation became increasingly clear in recent years. Moreover, we outline how deregulation of the GC transcriptional program can drive lymphomagenesis.